Sustainable valorization of yellow cherry juice using natural propolis and non-thermal techniques - Yıkmış, Seydi; Türkol, Melikenur; Tokatlı Demirok, Nazan; Tokatlı, Nazlı; Rüzgar, Ezgi; Mohamed Ahmed, Isam A.; Aljobair, Moneera O. (Frontiers in Sustainable Food Systems, 2025)
This study investigated the effects of propolis enrichment and thermosonication conditions on bioactive components, amino acid profile, antioxidant capacity and sensory properties of yellow cherry juice. Temperature (40–50°C), time (4–10 min), amplitude (40–80%) and propolis concentration (40–80 mg/100 mL) were optimized as independent variables using response surface methodology (RSM). Principal component analysis (PCA) analysis revealed that thermosonicated samples (TS-YCJ) were positively correlated with functional components such as chlorogenic acid, caffeic acid, epicatechin and total soluble solids (TSS). The malic acid content reached its highest level at 1,174.38 mg/L in thermosonicated optimized propolis yellow cherry juice (TS-YCJ), whereas this value remained at 1,078.34 mg/L in the pasteurized samples. Thermosonication application significantly increased the antioxidant capacity measured by total phenolic content (TPC), total flavonoid content (TFC) and DPPH radical inhibition. While TPC content reached 268.72 mg GAE/L in thermosonicated optimized propolis yellow cherry juice samples, it remained at 256.27 mg GAE/L in control samples. Among the phenolic compounds, chlorogenic acid (35.42 mg/L) and caffeic acid (12.67 mg/L) increased significantly after thermosonication. In terms of amino acid profile, components such as proline (42.21 mg/L), glycine (38.45 mg/L) and phenylalanine (24.32 mg/L) were found at higher levels in control samples. In sensory analysis, thermosonication samples received high scores in terms of taste, odor and overall acceptability. High R2 values (98.94–99.80%) reveal the strong explanatory power and reliability of the model. These findings indicate that thermosonication and propolis offer an effective combination to improve the functional properties, sensory quality and phenolic compound profile of yellow cherry juice.